2017
DOI: 10.4103/neuroindia.ni_151_16
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled study of operative versus nonoperative treatment for large spontaneous supratentorial intracerebral hemorrhage

Abstract: In patients with SSICH, mortality was found to be significantly associated with the treatment arm and the results were in favour of SM among the patients presenting with GCS 4-8, hematoma volume 31-60 ml, midline shift of more than 5 mm, and intraventricular extension of the hematoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 1 publication
2
18
0
3
Order By: Relevance
“…16 Quality of studies was low in 9 studies, 30,32,[34][35][36][38][39][40]45 and moderate in 8 studies. 33,37,[41][42][43][44]46,47 Only 4 studies were of high quality, 15,16,18,31 of which 2 investigated minimally invasive surgery (Fig 2). 18,31 The funnel plot suggested possible publication bias for smaller studies demonstrating results in favor of medical management (Fig 3).…”
Section: Resultsmentioning
confidence: 99%
“…16 Quality of studies was low in 9 studies, 30,32,[34][35][36][38][39][40]45 and moderate in 8 studies. 33,37,[41][42][43][44]46,47 Only 4 studies were of high quality, 15,16,18,31 of which 2 investigated minimally invasive surgery (Fig 2). 18,31 The funnel plot suggested possible publication bias for smaller studies demonstrating results in favor of medical management (Fig 3).…”
Section: Resultsmentioning
confidence: 99%
“…Rost et al12 concluded that ICH volumes are frequently used in clinical decision-making and categorized the volumes as <30 mL, 30–60 mL, and >60 mL. In Bhaskar’s study, the mortality rate at 3 months was found to be directly proportional to hematoma volume ( P =0.039); the mortality rates reported in this study were 56.4% among patients with hematoma volumes in the range of 31–60 mL, 81% for volumes in the range of 61–90 mL, and 100% for volumes >90 mL 13…”
Section: Discussionmentioning
confidence: 51%
“…Moreover, the Surgical Trial in Intracerebral Hemorrhage (STICH) studied 1,033 patients with SSICH and reported that there was no overall benefit of surgical intervention compared with nonsurgical management 4. However, in Mukesh’s study,13 the mortality rate at 3 months was significantly lower in the surgical group (61.8%) than in the conservative group (85.2%; P =0.043), and the mortality rate was significantly higher (80.5%) among patients with GCS scores of 4–8 compared with those with GCS scores of 9–14 (55%) among both the surgical and conservative treatment groups ( P =0.037). Furthermore, among patients with GCS scores of 4–8, the mortality rate of the surgical group (65.2%) was found to be significantly lower than that of the conservative therapy group (100%; P =0.005).…”
Section: Discussionmentioning
confidence: 99%
“…nme, tüm dünyada mortalite ve morbiditenin en önde gelen nedenlerinden biridir (1,2). İnmelerin ikinci en yaygın sebebi olan ve %10-55 arasında sıklık bildirilen spontan (non-travmatik) İSH olguları, etkin tedavi şeması net bir şekilde ortaya konamamış, mortalitesi son derece yüksek (ilk bir aylık ölüm oranı %30-50), gerek yüksek mortalite ve gerekse kalıcı morbidite nedeniyle toplumda önemli sosyo-ekonomik etkilere neden olan olgulardır (2)(3)(4)(5). İSH ile ilgili çalışmalara literatürde, diğer inme ve intrakranial kanama nedenlerine göre daha az rastlanmaktadır (6).…”
Section: unclassified
“…Hemorajik inmelerin ölüm oranı iskemik inmelere göre daha yüksektir ve mortal olmayan olgularda bile ciddi sekeller kalabilir. Hastaların sadece %20'si intraserebral kanamadan altı ay sonra kimseye ihtiyaç duymadan hayatını sürdürebilmektedir (5,8).…”
Section: unclassified